Marketing 4.0 for Mango Market Development Effectively in Indramayu Regency, Indonesia - Rusliati, Ellen; Mulyaningrum, Mulyaningrum; Rusyani, Erni; Mulyanto, Ferry (Universitas Mercu Buana, 2024)
Objectives: Entrepreneurs experienced a decline in sales during Covid-19. Digital marketing strategies could identify the desired products and services of their potential customers. Therefore, the objective of this study was to generate a market 4.0 model by integrating conventional and digital marketing with the 4C market mix, customer behavior, and the 5A approach (aware, appeal, asked, acted, advocate). Methodology: Descriptive and qualitative methods were used with atlas.ti software for data analysis. The study focused on mango farmers and entrepreneurs producing derived products in Indramayu Regency, Indonesia. In-depth interviews and participant observations were used to collect data. Finding: The research results showed that farmers and entrepreneurs who applied marketing 4.0 were able to survive during the COVID-19 pandemic, and were interested in continuing to develop the market in the future Conclusion: The use of digital technology in marketing activities is still at an early stage, which is limited to WhatsApp groups and websites. The use of marketing 4.0 has resulted in a wider marketing reach for Indramayu mangoes.